Ultrasensitive Troponin I and Incident Cardiovascular Disease. Issue 12 (3rd November 2022) - Empana, Jean-Philippe; Lerner, Ivan; Perier, Marie-Cécile; Guibout, Catherine; Jabre, Patricia; Bailly, Karine; Andrieu, Muriel; Climie, Rachel; van Sloten, Thomas; Vedie, Benoit; Geromin, Daniela; Marijon, Eloi; et al.
Abstract : Background: To examine the association of ultrasensitive cTnI (cardiac troponin I) with incident cardiovascular disease events (CVDs) in the primary prevention setting. Methods: cTnI was analyzed in the baseline plasma (2008–2012) of CVD-free volunteers from the Paris Prospective Study III using a novel ultrasensitive immunoassay (Simoa Troponin-I 2.0 Kit, Quanterix, Lexington) with a limit of detection of 0.013 pg/mL. Incident CVD hospitalizations (coronary heart disease, stroke, cardiac arrhythmias, deep venous thrombosis or pulmonary embolism, heart failure, or arterial aneurysm) were validated by critical review of the hospital records. Hazard ratios were estimated per log-transformed SD increase of cTnI in Cox models using age as the time scale. Results: The study population includes 9503 participants (40% women) aged 59.6 (6.3) years. cTnI was detected in 99.6% of the participants (median value=0.63 pg/mL, interquartile range, 0.39–1.09). After a median follow-up of 8.34 years (interquartile range, 8.0–10.07), 516 participants suffered 612 events. In fully adjusted analysis, higher cTnI (per 1 SD increase of log cTnI) was significantly associated with CVD events combined (hazard ratio, 1.18 [1.08–1.30]). Among all single risk factors, cTnI had the highest discrimination capacity for incident CVD events (C index=0.6349). Adding log cTnI to the SCORE 2 (Systematic Coronary Risk Evaluation) risk improved moderately discriminatory capacity (C index 0.698 versus 0.685; bootstrapped C index difference: 0.0135 [95% CI, 0.0131–0.0138]), and reclassification of the participants (categorical net reclassification index, 0.0628 [95% CI, 0.023–0.102]). Findings were consistent using the US pooled cohort risk equation. Conclusions: Ultrasensitive cTnI is an independent marker of CVD events in the primary prevention setting.